2018
DOI: 10.1016/j.jbiomech.2018.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of knee injury threshold during tibial compression based on limb orientation in mice

Abstract: Our previous studies used tibial compression overload to induce anterior cruciate ligament (ACL) rupture in mice, while others have applied similar or greater compressive magnitudes without injury. The causes of these differences in injury threshold are not known. In this study, we compared knee injury thresholds using a "prone configuration" and a "supine configuration" that differed with respect to hip, knee, and ankle flexion, and utilized different fixtures to stabilize the knee. Right limbs of female and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
0
3
1
Order By: Relevance
“…Conversely, other reports showed that a force of 12 N was required for ACL rupture in C57BL/6 mice using a compression device 17, 18 . We obtained a lower force value than the previous study using a compression device, which may be attributed to differences in the knee flexion degree and contact of the joint surfaces 23 . No histological, macroscopic, or morphological differences were found between the INTACT and ACL-R groups.…”
Section: Discussioncontrasting
confidence: 88%
“…Conversely, other reports showed that a force of 12 N was required for ACL rupture in C57BL/6 mice using a compression device 17, 18 . We obtained a lower force value than the previous study using a compression device, which may be attributed to differences in the knee flexion degree and contact of the joint surfaces 23 . No histological, macroscopic, or morphological differences were found between the INTACT and ACL-R groups.…”
Section: Discussioncontrasting
confidence: 88%
“…( 49,50 ) Previously we showed that the ACL was not directly damaged by a single bout of cyclic loading and no structural damage to cartilage, bone, ligaments, or other joint tissues was present at 1 h following loading. ( 37 ) Given the repeatable nature of the cyclic loading model and work examining ACL damage in various loading configurations, ( 51 ) we are confident that the ACL was not ruptured by loading in the present study. However, a single bout of loading could have induced a subcritical level of damage to the ACL and other tissues that initiated further joint degradation.…”
Section: Discussionmentioning
confidence: 66%
“…S1). Another possible fixturing approach is to make custom‐molded pads from hardened modeling clay or PMMA . This approach would allow a snug fit for the foot and knee but would require different sets of molds for mice of different age, sex, or genotype.…”
Section: Implementing the Mouse Axial Compression Tibial Loading Modelmentioning
confidence: 99%